Modes of occurrence and influencing factors of lithium in Li-rich coal from the Jungar coalfield, China, insights of LA-ICP-MS - Huidi Hao; Bo Jiu; Wenhui Huang; Mingzhe Sun (International Journal of Coal Science & Technology)
Abstract Due to the limitations of widely used energy spectrum and spectral analyses for the determination of trace elements in coal, the modes of occurrence of Li still remains unclear. This study investigated the distribution of Li in selected bulk samples and in-situ kaolinite particles in the No.6 Li-rich coals from the Haerwusu Mine of the Jungar Coalfield using ICP-MS and LA-ICP-MS. The results reveal an elevated Li concentration in the lower section of the No.6 coal with high Sr/Ba ratio compared to the upper section with more terrigenous mudstone along the vertical profile. LA-ICP-MS mapping and spot analyses results showed that Li was concentrated in kaolinite but occur in variations in the concentrations of Li among different types of kaolinite. The concentration of Li in kaolinite is ranked as follows: cryptocrystalline kaolinite (2225.83 ppm) > vermicular kaolinite (651.49 ppm) > altered K-bearing kaolinite (593.44 ppm) > clastic kaolinite (478.68 ppm). The in-situ concentration of Li in kaolinite is much higher than that of the bulk samples, indicating that kaolinite is the dominant host mineral for Li as well. The Al2O3/TiO2 and Nb/Yb-Zr/TiO2 ratios indicate that Li in No. 6 coal primarily originated from Paleoproterozoic granite in the Yinshan Mountain and felsic volcanic ash. Seawater leaching has a critical influence on the redistribution of Li in the coal from the Haerwusu Mine or even the whole Jungar Coalfield.